Arterial thromboembolism in a feline without cardiac changes: Case report - Braga Mendes, Julia; Fregati Santos, Andressa; Duarte Minanti, Caroline; do Carmo, Vanessa (Pubvet, 2023)
Arterial thromboembolism (ATE) is a clinically challenging condition that affects feline health, with a higher incidence in cats with heart disease. This case report presents a less common scenario, where a four-year-old feline with no history of heart problems was diagnosed with ATE. The animal was treated at a Veterinary Center in the city of São Paulo (Brazil), in a state of emergency, with complaints of acute paraplegia and intense pain in the pelvic limbs. Before the event, the cat was in good health, with normorexia, normodipsia, normuria and normochesia. Analgesia and sedation were performed to control pain and provide better assessment, and the absence of superficial or deep pain was identified in both pelvic limbs during the physical examination. The patient was referred to hospitalization for pain control, blood collection, imaging and cardiological tests for screening. Through tomography, a mass (thrombus/embolus) was identified in the right iliac artery. During the entire hospitalization period, the patient underwent specific protocols for ATE and, after stabilization of the condition, surgical thrombectomy intervention was indicated. The procedure occurred without complications, and the patient remained hospitalized for another 2 (two) days for evaluation and evolution of the clinical condition, being released with assisted discharge, physiotherapy recommendations and weekly returns for definitive discharge.